Domestic water demand: A case study in Kluang, Johor - Sabirah, Sulaiman (2013)
Demand for water is a vital issue in Malaysia as population growth, agricultural, and industrial development takes place. In addition, some states face problems of water shortage and stress because water use is already reaching maximum demand levels like Selangor state. In Johor, supply shortage is not a common problem faced by the water supply department, but as early steps it is essential for improving the security and resilience of our nation's drinking water and wastewater infrastructures. It was estimated a bout 40% of the world's population currently lives in water stressed areas. With a global population increase of three billion people predicted by 2050, water scarcity will soon become a matter of life or death. Economist, therefore have become interested in understanding the empirical nature of water demand for the accurate forecasting of water demand, pricing and in improving water resource planning and management. Significant actions should be taken to assess and reduce water loss and develop new security technologies to detect and monitor contaminants and prevent security breaches in water demand. The purpose of this study is to examine the relationship between price and quantity and other relevant variables for water consumption in Kluang, Johor. One panel data regression between consumption and expenditure of water was estimated and the result indicates that price and quantity of water demanded have a positive relationship where increase in price will leads to increase in water use because the use of average price in this study. The regressions give the best result because it takes care of heterogeneity of individual in this analysis and the elasticities of price in range of 0.66 to 0.65 respectively. Furthermore, five different price and other variables specification regression models for a cross sectional analysis of a 335 samples of households, indicated that the price is significant at one percent level in all the regression in the models. The models explain more than 80 percent of the variation in the water use in the year 2012. The social and cultural practices were also found to affect the consumption patterns of the three major different ethnic groups in Malaysia. The Malay community in the sample was found to consume more water than the Chinese and Indian communities respectively. Results of the study indicate that water pricing has a great potential of being an effective policy tool for water supply authorities. Price could be used to allocate and use water efficiently and could play a key role in the long run planning and conservation of water supplies. In this study, price variable is statistically significant at one percent level. This result shows that price charge for water will influence the total demand that have to be met by suppliers. The investments that have to be made by the authority will depend on the demand it has to fulfill. In addition, the demand is a function of price charged, a direct relationship between pricing policy and the scale of the investment is established. Thus, the water authority can make use of the simulated models to estimate the size of the facilities to be produced in order to make an efficient investment decision for future plan. The structured tariff mechanism was the most appropriate way to increase efficiency in the industry